Pengaruh Etos Kerja Guru terhadap Kinerja Guru TK - Lia Puji Lestari; Ghufron Abdullah; Ngurah Ayu Nyoman Murniati (Journal Prakarsa Paedagogia, 2022)
The purpose of this study was to analyze the effect of work ethic on the performance of Kindergarten teachers in Bergas District, Semarang Regency. The population in this study were kindergarten teachers in Bergas District, Semarang Regency, which amounted to 153 people, with a sample of 110 people using a proportional random sample. The method used for data collection is a questionnaire method. The data analysis used was prerequisite test and hypothesis testing which included multiple linear regression analysis to determine the effect of work ethic and classroom management on teacher performance. Data analysis used IBM SPSS Statistics 23. The results showed: (1) Work ethic has a positive and significant effect on the performance of Kindergarten teachers in Bergas District, Semarang Regency with an F-count of 9.400 and has a significance less than 0.05 (sig 0.003 < 0.05). Based on these results, the research hypothesis which states that there is an influence of work ethic on the performance of Kindergarten teachers in Bergas District, Semarang Regency is accepted